Design and Evaluation of a Cooperative-Schedule Priority Transmission Protocol for Image Transmission in WISNs - van Khoe Ta; Ic-Pyo Hong (IEEE Access)
Wireless image sensor networks equipped with tiny cameras face significant challenges in achieving reliable, timely, and energy-efficient image transmission due to the bursty nature of image data and the limitations of sensor nodes. This research introduces a cooperative-schedule priority transmission protocol (CSPTP), designed to overcome these challenges. CSPTP leverages a multi-resolution discrete wavelet transform to compress captured images, decomposing them into sub-bands with varying levels of importance. The protocol establishes a data path consisting of path nodes and cooperative nodes to efficiently manage the bursty nature of image packets. Priority levels are assigned to nodes based on their roles in image transmission and to packets based on their importance in image reconstruction. Nodes collaborate through overhearing, which enhances transmission reliability and accelerates packet delivery. The proposed protocol was rigorously evaluated through comparative analyses and experimental validation. Analytical results demonstrated that CSPTP significantly reduces image transmission time and balances energy consumption, outperforming existing protocols. Experimental validation further confirmed substantial improvements in packet delivery reliability, achieving success rates of 99.5% for important packets and 98.3% for other packets when the source multimedia node is at level five, and 99% and 96%, respectively, at level eight.